CONSORT extension for reporting within-person randomised trials - Pandis, N; Chung, B; Scherrer, R; Elbourne, D; Altman, D (BMJ Publishing Group, 2017)
Evidence shows the quality of reporting of randomised controlled trials (RCTs) is not optimal. The lack of transparent reporting impedes readers from judging the reliability and validity of trial findings, researchers from extracting information for systematic reviews and results in research waste. The Consolidated Standards of Reporting Trials (CONSORT) Statement was developed to improve the reporting of randomised controlled trials. Within-person trials are a particular type of trial for conditions that can affect two or more body sites, and are a useful and efficient tool because the comparisons between interventions are within-persons. Such trials are more commonly conducted in ophthalmology, dentistry and dermatology. The reporting of within-person trials has, however, been variable and incomplete, hindering their usefulness in clinical decision making and by future researchers. This document presents the CONSORT extension to within-person trials. It aims to facilitate the reporting of within-person trials. CONSORT within-person extends 16 items of the CONSORT 2010 checklist, and introduces a modified flowchart and baseline table to enhance transparency. Examples of good reporting and evidence-based rationale for CONSORT within-person checklist items are provided.